Regional Planning Between Theory and Practice - Jahan, Mostafa Mansour ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2025)
This study highlights the critical role of regional planning in advancing economic, social, and spatial development by promoting balanced growth and reducing disparities between regions. Regional planning has proven to be an effective tool, as demonstrated by early applications in Russia in 1928 and in countries like the United Kingdom during the 1929 Great Depression. Following independence, many developing countries also adopted planning strategies to revitalize their economic sectors. The study addresses key questions related to the definition of regional planning, its connection to geography, influencing factors, foundational principles, and the relevance of Central Place Theory to planning efforts. The research aims to clarify the role of regional planning in economic development, its interdisciplinary nature, and the contribution of Central Place Theory to planning frameworks. The paper is structured around two main themes: the first examines the concept and scope of regional planning and its links to other sciences; the second explores Central Place Theory and its application within regional planning.